1987
DOI: 10.1002/cne.902590209
|View full text |Cite
|
Sign up to set email alerts
|

Choline acetyltransferase‐immunoreactive neurons and terminals in the rat septal complex: A combined light and electron microscopic study

Abstract: A monoclonal antibody against choline acetyltransferase (ChAT), the acetylcholine synthesizing enzyme, was used to determine the morphological characteristics of cholinergic neurons and axon terminals within the rat septum. Light microscopy revealed numerous large fusiform or multipolar ChAT-immunoreactive neurons in the medial septal nucleus/diagonal band complex (MSDB). In contrast, virtually no immunostained cells were found in the lateral septum (Nc. septalis dorsalis and Nc. septalis lateralis). Fine immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(44 citation statements)
references
References 51 publications
5
37
2
Order By: Relevance
“…In rat, the existence of intraseptal cholinergic collateral projections onto GABAergic neurons, born out of lesioning and ultrastructural studies (Onteniente et al, 1986(Onteniente et al, , 1987Bialowas and Frotscher, 1987;Leranth and Frotscher, 1989;Brauer et al, 1998), is consistent with the notion of a muscarinic tone in the MS/DB . Although equivalent information in mouse is lacking, the pharmacological data presented in this study provide evidence for noncholinergic neurons being subject to a muscarinic tone in the mouse MS/DB.…”
Section: Differential Effects Of Ngf On Cholinergic Neurons and Nonchsupporting
confidence: 72%
See 2 more Smart Citations
“…In rat, the existence of intraseptal cholinergic collateral projections onto GABAergic neurons, born out of lesioning and ultrastructural studies (Onteniente et al, 1986(Onteniente et al, , 1987Bialowas and Frotscher, 1987;Leranth and Frotscher, 1989;Brauer et al, 1998), is consistent with the notion of a muscarinic tone in the MS/DB . Although equivalent information in mouse is lacking, the pharmacological data presented in this study provide evidence for noncholinergic neurons being subject to a muscarinic tone in the mouse MS/DB.…”
Section: Differential Effects Of Ngf On Cholinergic Neurons and Nonchsupporting
confidence: 72%
“…In rat, the presence of an ambient level of acetylcholine in the MS/DB is supported by neuroanatomical and electrophysiological evidence, and ultrastructural studies have demonstrated intraseptal cholinergic synapses on GABAergic neurons in the MS/DB (Bialowas and Frotscher, 1987;Leranth and Frotscher, 1989;Brauer et al, 1998;Alreja et al, 2000;Wu et al, 2000). In this study, to demonstrate the presence of ambient acetylcholine in mouse, the acetylcholine esterase inhibitor neostigmine was applied onto MS/DB neurons while the rate of spontaneous firing was monitored.…”
Section: Enhanced Acetylcholine Release Mediates the Rapid Effect Of mentioning
confidence: 84%
See 1 more Smart Citation
“…Secondly, we wanted to reveal co-localization and the spatial relationship of the VGLUT3-ir PBs with well-defined neuron subpopulations and/or the fiber systems projecting to and passing the LS. Thus, we performed single and double immunofluorescence staining of VGLUT3 and the calcium-binding proteins calbindin (CALB), calretinin (CALR) and parvalbumin (PARV), with choline acetyltransferase (ChAT), tyrosine hydroxylase (TH) and tryptophan hydroxylase (TrpH), and with Wisteria floribunda agglutinin (WFA) revealing perineuronal nets (Bialowas and Frotscher, 1987;Gall and Moore, 1984;Jacobowitz and Winsky, 1991;Kiss et al, 1997;Seeger et al, 1994;Seifert et al, 1998). Triple labeling of VGLUT3 with VGLUT1 and VGLUT2 was performed, as the LS is known to be positive for both glutamatergic markers and it was recently suggested, that projection neurons in the intermediate and ventral LS use glutamate as neurotransmitter (Kaneko et al, 2002;Kocsis et al, 2003;Lin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The morphological characteristics of nitrergic neurons in the MS (large indented nucleus and narrow cytoplasmic rim) and the rarity of synaptic contacts on their somata suggest that they should be cholinergic neurons. Bialowas and Frotsher [10] have shown that ChAT-immunoreactive neurons possess large nuclei with multiple invaginations of the nuclear membrane and terminals rarely were found in synaptic contact on the cell bodies of positive neurons. This is further supported by the result of Kitchener and Diamond [26]: they had shown that 97% of NADPH-diaphorase reactive neurons in the MS/DB were choline acetyltransferase immunoreactive.…”
Section: Discussionmentioning
confidence: 99%